2016
DOI: 10.1186/s13012-016-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting implementation of perinatal mental health screening in women of refugee background

Abstract: BackgroundFor women of refugee background, the increased risk of mental illness associated with pregnancy is compounded by pre- and post-settlement stressors. In Australia, antenatal screening for depression and anxiety symptoms using the Edinburgh Postnatal Depression Scale is recommended for all women. Despite this, screening is not routinely implemented and little is known about barriers and enablers to implementation for women of refugee background.MethodsSemi-structured interviews were conducted with a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(111 citation statements)
references
References 33 publications
2
106
0
Order By: Relevance
“…Six studies evaluated the impact of pre-and post-qualification training (Elliott, Ross-Davie, Sarkar, & Green, 2007; Higgins, Carroll, & Sharek, 2012;Higgins, Carroll, & Sharek, 2016;Jardri et al, 2010;Lau, McCauley, Moss, Miles, & Cross, 2015;McLachlan, Forster, Collins, Gunn, & Hegarty, 2011). Two looked at specific groups of women: black and ethnic minority women (Edge, 2010) and those with a refugee background (Nithianandan et al, 2016). Midwives' involvement in, and views of, PMH screening and assessment were examined in five studies (Rollans, Schmied, Kemp, & Meade, 2013a;Rompala, Cirino, Rosenberg, Fu, & Lambert, 2016;Williams, Turner, Burns, Evans, & Bennert, 2016;Yamashita et al, 2007;Yelland, McLachlan, Forster, Rayner, & Lumley, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies evaluated the impact of pre-and post-qualification training (Elliott, Ross-Davie, Sarkar, & Green, 2007; Higgins, Carroll, & Sharek, 2012;Higgins, Carroll, & Sharek, 2016;Jardri et al, 2010;Lau, McCauley, Moss, Miles, & Cross, 2015;McLachlan, Forster, Collins, Gunn, & Hegarty, 2011). Two looked at specific groups of women: black and ethnic minority women (Edge, 2010) and those with a refugee background (Nithianandan et al, 2016). Midwives' involvement in, and views of, PMH screening and assessment were examined in five studies (Rollans, Schmied, Kemp, & Meade, 2013a;Rompala, Cirino, Rosenberg, Fu, & Lambert, 2016;Williams, Turner, Burns, Evans, & Bennert, 2016;Yamashita et al, 2007;Yelland, McLachlan, Forster, Rayner, & Lumley, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sub-themes in this domain were time pressures, referral pathways and further services, the organization of maternity care, training and support for midwives. Many midwives said that time pressures made assessment and care more challenging and could be a barrier to effective assessment (Edge, 2010;Lees et al, 2009;Nithianandan et al, 2016;Phillips, 2015;Rompala et al, 2016). Some felt that caring for women with PMH problems required additional time (McCauley et al, 2011;Mivšek et al, 2008).…”
Section: Infrastructurementioning
confidence: 99%
“…It has also been found that prenatal depression among refugee women has been poorly documented, even though they have unique life stressors that make them more vulnerable to prenatal depression (24,25). Des Moines, Iowa is a city in the United States that has resettled refugees for over 40 years (26).…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study looked at the factors that affect the implementation of prenatal depression screening for women of refugee backgrounds, as the prevalence of prenatal depression among this population is poorly documented (25). The study found that participants recognized a need for mental health screening, although this may have been due to selection bias meaning those who participated were more likely to understand the need for screening (25). Des Moines, Iowa has been an official refugee resettlement city since 1975, resettling people from Southeast Asia, Eastern…”
Section: Prenatal Depression In Refugee Populationsmentioning
confidence: 99%
See 1 more Smart Citation